(untitled) (Innovations in Environmental Economics, 2025)
The transition toward sustainable agriculture has intensified global attention on the environmental and economic implications of agrochemical use. Agrochemicals remain vital for food security, yet their misuse contributes to soil degradation, pollution, and greenhouse gas emissions. This study employs a bibliometric approach to examine global research trends, collaboration patterns, and thematic developments linking agrochemicals with environmental sustainability and the green economy. Data were retrieved from the Scopus database covering the period 1976–2025 and analyzed using performance indicators, co-authorship, co-citation, and keyword co-occurrence mapping. The results reveal a continuous increase in publications and citations, particularly after 2018, reflecting the growing relevance of sustainable agricultural practices. Europe and North America dominate scientific output and influence, while developing regions show emerging but limited participation. Thematic analysis indicates a paradigm shift from productivity-driven studies to sustainability-oriented research emphasizing biochar, nutrient recycling, and circular agriculture. Reference co-citation patterns further highlight the integration of environmental policy, agronomic innovation, and economic frameworks.These findings provide a holistic overview of how scientific communities have evolved to address the dual challenge of agricultural productivity and environmental protection. The study contributes to future research and policy formulation by identifying emerging directions for sustainable agrochemical management and reinforcing the need for equitable global collaboration in the transition toward a low-carbon agricultural economy.